Soil radon survey to assess NAPL contamination from an ancient spill. Do kerosene vapors affect radon partition ?. (May 2017) - De Simone, Gabriele; Lucchetti, Carlo; Pompilj, Francesca; Galli, Gianfranco; Tuccimei, Paola; Curatolo, Pierpaolo; Giorgi, Riccardo
Abstract: A soil radon-deficit survey was carried out in a site polluted with kerosene (Rome, Italy) in winter 2016 to assess the contamination due to the NAPL residual component in the vadose zone and to investigate the role of the vapor plume. Radon is indeed more soluble in the residual NAPL than in air or water, but laboratory experiments demonstrated that it is also preferentially partitioned in the NAPL vapors that transport it and may influence soil radon distribution patterns. Specific experimental configurations were designed and applied to a 31-station grid to test this hypothesis; two RAD7 radon monitors were placed in-series and connected to the top of a hollow probe driven up to 80-cm depth; the first instrument was directly attached to the probe and received humid soil gas, which was counted and then conveyed to the second monitor through a desiccant (drierite) cylinder capturing moisture and eventually the NAPL volatile component plus the radon dissolved in vapors. The values from the two instruments were cross-calibrated through specifically designed laboratory experiments and compared. The results are in agreement within the error range, so the presence of significant NAPL vapors, eventually absorbed by drierite, was ruled out. This is in agreement with low concentrations of soil VOCs. Accordingly, the radon-deficit is ascribed to the residual NAPL in the soil pores, as shown very well also by the obtained maps. Preferential areas of radon-deficit were recognised, as in previous surveys. An average estimate of 21 L (17 Kg) of residual NAPL per cubic meter of terrain is provided on the basis of original calculations, developed from published equations. A comparison with direct determination of total hydrocarbon concentration (23 kg per cubic meter of terrain) is provided. Highlights: A soil radon survey was carried out to assess kerosene contamination. The role of vapors on radon transport and distribution was investigated. A specific field experimental configuration was designed and calibrated. Fraction of residual NAPL in soil pores was quantified using original calculations. The map of radon-deficit corresponds very well to that of residual NAPL fraction.